(untitled) - Byham, William C. (New York, 1988)
Most managers know that revitalization in their companies must occur from the ground up. But how to get that message to employees without applying the kind of pressure that makes them even less productive? The answer is empowerment. In this motivating book, you will find specific strategies designed to help you encourage responsibility, acknowledgment, and creativity so that employees feel they "own" their jobs. It's all here, in an accessible guide for the successful managers of tomorrow.
Keywords: Employee empowerment.,Communication in management.,Interpersonal relations